Polycystic ovarian syndrome and the risk of subsequent primary ovarian insufficiency: a nationwide population-based study. Issue 7 (July 2017) - Pan, Mei-Lien; Chen, Li-Ru; Tsao, Hsiao-Mei; Chen, Kuo-Hu
Abstract: Objective: To evaluate the risk of subsequent primary ovarian insufficiency (POI) amongst patients with a history of polycystic ovarian syndrome (PCOS). Methods: This nationwide, population-based study is an inspection and review of data from the 1998 to 2012 Taiwan National Health Insurance Research Database. In a sample of 1, 000, 000 randomly sampled individuals, women with PCOS (exposure group; n = 7, 049) and women without PCOS (contrast group; n = 70, 490) were compared. Women initially diagnosed with PCOS at less than 15 or more than 35 years of age were excluded. Each woman with PCOS was age-matched to 10 women without PCOS. The diagnoses of PCOS and POI (coded using International Classification of Diseases, 9th Revision, Clinical Modification) were further confirmed with blood test results and ultrasonographic findings to ensure the accuracy of the diagnoses. Results: POI occurred more among women with PCOS compared with women without PCOS (3.73% vs 0.44%; P < 0.001). Using Kaplan-Meier survival analysis, the POI-free survival rates were significantly different between the exposure and contrast groups ( P < 0.001). During 10 years of follow-up, Cox proportional-hazard analysis revealed that the risk for POI was significantly higher in the exposure than in the contrast group (hazard ratio [HR] 8.64, 95% confidence interval [CI] 7.33-10.18) and remained similar after adjustment for covariates (adjusted HR 8.31, 95% CI 7.05-9.81). Compared with that of women without PCOS, the risk of POI was even higher for women with PCOS who did not receive metformin treatment (adjusted HR 9.93, 95% CI 8.28-11.90). However, the risk for POI was significantly reduced for women with PCOS who received metformin treatment (adjusted HR 5.66, 95% CI 4.36-7.35). Conclusions: As a possible precursor stage, prior PCOS is a significant and independent risk factor for development of POI. The use of metformin reduces the risk of POI.